General Caspase Inhibition in Primary Chondrogenic Cultures Impacts Their Transcription Profile Including Osteoarthritis-Related Factors - Vesela, Barbora; Zapletalova, Martina; Svandova, Eva; Ramesova, Alice; Doubek, Jaroslav; Lesot, Hervé; Matalova, Eva (Cartilage, 2021)
OBJECTIVE: The knowledge about functions of caspases, usually associated with cell death and inflammation, keeps expanding also regarding cartilage. Active caspases are present in the growth plate, and caspase inhibition in limb-derived chondroblasts altered the expression of osteogenesis-related genes. Caspase inhibitors were reported to reduce the severity of cartilage lesions in osteoarthritis (OA), and caspase-3 might represent a promising biomarker for OA prognosis. The objective of this investigation was to decipher the transcriptomic regulation of caspase inhibition in chondrogenic cells. DESIGN: Limb-derived chondroblasts were cultured in the presence of 2 different inhibitors: Z-VAD-FMK (FMK) and Q-VD-OPH (OPH). A whole transcriptome RNA sequencing was performed as the key analysis. RESULTS: The analysis revealed a statistically significant increase in the expression of 252 genes in the FMK samples and 163 genes in the OPH samples compared with controls. Conversely, there was a significant decrease in the expression of 290 genes in the FMK group and 188 in the OPH group. Among the top up- and downregulated genes (more than 10 times changed), almost half of them were associated with OA. Both inhibitors displayed the highest upregulation of the inflammatory chemokine Ccl5, the most downregulated gene was the one for mannose receptors Mrc1. CONCLUSIONS: The obtained datasets pointed to a significant impact of caspase inhibition on the expression of several chondro-/osteogenesis-related markers in an in vitro model of endochondral ossification. Notably, the list of these genes included some encoding for factors associated with cartilage/bone pathologies such as OA.
Keywords: Osteoarthritis; chondroblasts; chondrocyty; lidé; osteoarthritis; osteoartróza; kaspasy; Caspases; chondrogeneze; RNA sequencing; caspase inhibitors; Chondrocytes; inhibitory kaspas; Caspase Inhibitors; Chondrogenesis; Humans